2015
DOI: 10.5851/kosfa.2015.35.6.815
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Models to Predict Listeria monocytogenes Growth at Low Concentrations of NaNO2and NaCl in Frankfurters

Abstract: This study developed probabilistic models to describe Listeria monocytogenes growth responses in meat products with low concentrations of NaNO2 and NaCl. A five-strain mixture of L. monocytogenes was inoculated in NBYE (nutrient broth plus 0.6% yeast extract) supplemented with NaNO2 (0-141 ppm) and NaCl (0-1.75%). The inoculated samples were then stored under aerobic and anaerobic conditions at 4, 7, 10, 12, and 15℃ for up to 60 d. Growth response data [growth (1) or no growth (0)] for each combination were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Because the predictions from the developed probabilistic models were expressed as numbers, growth was determined at more than 0.5 of growth probability (Yoon et al , 2012). In addition, growth responses (growth or no growth) from the sausages were determined at 1 Log CFU/g of S. aureus growth (Gwak et al , 2015; Koutsoumanis et al , 2004). Comparisons between predicted and observed growth response are presented in Table 3; the observed growth responses mostly agreed with the predicted growth responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the predictions from the developed probabilistic models were expressed as numbers, growth was determined at more than 0.5 of growth probability (Yoon et al , 2012). In addition, growth responses (growth or no growth) from the sausages were determined at 1 Log CFU/g of S. aureus growth (Gwak et al , 2015; Koutsoumanis et al , 2004). Comparisons between predicted and observed growth response are presented in Table 3; the observed growth responses mostly agreed with the predicted growth responses.…”
Section: Resultsmentioning
confidence: 99%
“…During storage, S. aureus cell counts were enumerated on MSA (Becton, Dickinson and Company). If the S. aureus cell count increased by more than 1 Log CFU/g compared with that on day 0, the result was considered to be “growth”, otherwise “no growth” was recorded (Gwak et al , 2015; Koutsoumanis et al , 2004). …”
Section: Methodsmentioning
confidence: 99%
“…Thirty frankfurters were immersed in 500 mL inoculum (3 log CFU/mL) in a sterilized plastic container for 2 min. The samples were air-dried under a laminar flow cabinet for 15 min to allow Salmonella attachment then transferred into vacuum bags ( Gwak et al, 2015 ). The bags were sealed for aerobic storage or vacuum packaged for anaerobic storage using a vacuum packager (HFV-500; Fujee Inc., Hwaseong, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, microbiological safety of processed meat products with lower nitrite levels can be improved by a combination of pH and sodium chloride concentration. Gwak et al [ 7 ] and Tompkin [ 40 ] have also suggested that increased sodium chloride levels can control the growth of harmful bacteria in processed meat products with lower nitrite concentrations because the antimicrobial effect of nitrite is influenced by sodium chloride concentration, pH, reductants, iron content, and so on.…”
Section: Combinations To Improve Microbiological Inhibitionmentioning
confidence: 99%
“…Meat products with lower nitrite (below conventional concentration of products) concentrations have been produced [ 5 ]. However, Doyle and Glass [ 6 ], and Gwak et al [ 7 ] have suggested that there are problems related to microbial safety of processed meat products with no or low nitrite concentrations. Therefore, the objective of this short communication was to review food safety of processed meat products formulated with no or low nitrite concentrations.…”
Section: Introductionmentioning
confidence: 99%